A política de saúde no enfrentamento ao trabalho precoce - Rocha, Gabriela Fernandes (2017)
The present thesis has as general objective to analyze health policy as a guarantee of rights when coping with child labor. The thesis is that there is no confrontation with early work in the field of health policy, since there is no policy of full care for children and adolescents that come from child labor. The theoretical contribution is Social Policies and Historical-Cultural Theory. As methodological procedures a documentary research was carried out, in which were analyzed work accidents datasheets, made available by CEREST, semi-structured interviews with health professionals from UBS and the field journal. The datasheets were analyzed through frequency extracted from SPSS and the interviews were analyzed through content analysis with the QDA Miner assistance. The work accidents datasheets show that children and adolescents who got injured had between 9 and 17 years old and performed activities in commerce and service, auxiliaries of various work branches, construction, agriculture and industry. The means that health professionals from UBS give to child labor is that is good to occupy, good to be responsible, necessary, important to help parents, it is not wrong if it is not forced and that a child should not have an adult responsibility. In relation to the existence of precocious work the great majority affirms that it does not exist. Professionals affirm that the procedure is (or should be) based in actions such as: family guidance, contact CRAS, contact the team, support the permanence in work, do nothing because it is a social problem. The care they perform is related to childcare, health education, health in school program, prenatal, oral health, women’s health, HPV vaccination, sexual life. The social demand related are: drug use/traffic, lack of care and hygiene, lack of leisure, teenage pregnancy, do not go to school, poverty, alcoholism, elderly abandonment. Professionals do not have specific formation to act against child labor. When asked about the notification, they reaffirmed that there was no child labor, so they were asked how they would report if they found children and adolescents working; the answers were: are unaware of notification, do not notify, the responsibility belongs to the nurse, notify (or should notify) the tutelary council, CRAS, the district and do not notify for fear of lack of confidentiality. It is considered that there is no confrontation against early work in health policy, at least not in basic care range, since there is no preparation and qualification for the basic health units professionals, nor full care policy for children and teenagers that come from child labor, since politics constitutes itself as a supporter of the process of social inequality.